2005
DOI: 10.1103/physrevc.71.044903
|View full text |Cite
|
Sign up to set email alerts
|

Productions of hadrons, pentaquarksΘ+andΘ*++, and di-baryon

Abstract: The hadron production in relativistic heavy ion collisions is well described by the quark combination model. The mixed ratios for various hadrons and the transverse momentum spectra for long-life hadrons are predicted and agree with recent RHIC data. The production rates for the pentaquarks Θ + , Θ * ++ and the di-baryon (ΩΩ) 0 + are estimated, neglecting the effect from the transition amplitude for constituent quarks to form an exotic state.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 91 publications
1
9
0
Order By: Relevance
“…In Fig. 1, we show the results of R B/M (z) and RB /M (z) which reproduce the numerical results of SDQCM [26].…”
supporting
confidence: 73%
See 1 more Smart Citation
“…In Fig. 1, we show the results of R B/M (z) and RB /M (z) which reproduce the numerical results of SDQCM [26].…”
supporting
confidence: 73%
“…This linearity is supported by the RHIC data, which show that the multiplicity of charged particles in central and semicentral nucleus-nucleus collisions is of nearly linear proportion to the number of participant nucleons N part [24] while thep/π − yield ratio, even at LHC energies [12], is almost independent of N part [7,25]. Calculations of the quark combination model developed by the Shandong Group (SDQCM) [26] also support such a property. Letting λ is a not very small auxiliary parameter, we thus have…”
mentioning
confidence: 57%
“…A quark and an antiquark neighboring in phase space form a meson and three quarks (antiquarks) form a baryon (antibaryon). Relativistic heavy-ion collisions produce a large volume of deconfined quark matter and this makes QCM to be a natural scenario for hadronization [31][32][33][34][35][36][37][38][39][40][41].…”
Section: Hadron Yields and P T Spectra In Qcmmentioning
confidence: 99%
“…In the latest work [28], we found that the data of p T spectra of identified hadrons in p-Pb collisions at √ s NN = 5.02 TeV [7,9,10,26,27] released by ALICE collaboration exhibit a striking quark number scaling. This scaling property is a direct consequence of quark (re-)combination mechanism (QCM) at hadronization [29][30][31][32][33][34], and it indicates the constituent quark degrees of freedom play an important rule in hadron production of small systems produced at LHC energies. We surprisingly found that quark number scaling seems to also hold in 40-60% and 60-80% multiplicity classes of p- * shaofl@mail.sdu.edu.cn † songjun2011@jnxy.edu.cn Pb collisions where the charged-particle multiplicity density at mid-rapidity is relatively small, i.e., dN ch /dη ∼ 10 − 20.…”
Section: Introductionmentioning
confidence: 99%
“…The main method is to compare results of various hadronization models with the data, and the future Z 0 factory is very suitable for this purpose. The popular hadronization models at the market, Lund String Fragmentation Model (LSFM) [ [7][8][9][10]. QCM was first proposed by Annisovich and Bjorken et al [11].…”
Section: Introductionmentioning
confidence: 99%